Guy Bleus : Mail-Art Memorabilia: T.A.C.- 42.292. - Bleus, Guy; Postmuseum, Brussel; Musée Postal, Bruxelles (Wellen : The Administration Centre, 1995)
The exhibition "Mail-Art Memorabilia" shows a wild historic and global vision about the reciprocal activities of the transnational and eternal Mail-Art network. The works and documentation of more than 260 mail-artists from 28 countries are a part of the huge archive of "The Administration Centre-42.292". E.G., artists'books, catalogues, mail-objects, fan-art, audio-art, postcards, artistamps, envelopes, copy-art, rubberstamp-art, e-mail-art,... and other memorabilia.
Engels
Guy Bleuys: Mail-Art Memorabilia : T.A.C.-42.292. Postmuseum, Brussel/ Musée Postal, Bruxelles, van/de 14-10-1995 tot/Au 5/11/1995. In de erezaal presenteert Guy Bleus "Mail-Art Memorabilia" uit zijn archief T.A.C.-42-292 / Dans le salon d'honneur Guy Bleus présente "Mail-Art Memorabiliaé provenant de ses archives T.A.C.-42.292
boek
Keywords: Bleus, Guy